Measurements Of The Patient's External Dose Rate Before, During, And After F-18 Fdg During Pet/Ct Imaging (Journal of Pharmaceutical Negative Results, 2022)
Now a days, positron emission tomography/computerized tomography is one of the most frequently used tests for screening patients having cancer. The test is done forty to sixty minutes following the intravenous injection of fluorine-18 deoxyglucose or 18F FDG, which is the most commonly used radiopharmaceutical in this imaging technique. Radiation is transferred to the atmosphere once the injection is performed; the released dose differs based on the activity of the substance being injected into the patient. The goal of this research was to evaluate the emitted radiation dose in subjects who were injected with F18-FDG intravenously and conclude a suitable discharge time following the performance of the PET/CT imaging technique for the patients. A total of fifty patients, twenty-nine females and twenty-one males participated in this study. They were sent to the department of nuclear medicine for fluorine-18 deoxyglucose positron emission tomography/computerized tomography test. The rate of the radiation doses was calculated at a distance of zero, hundred, and two-hundreds centimetres from patients using a radiation survey meter at 4 different times, including:1-Following the IV injection of fluorine-18 deoxyglucose ,2-Prior to positron emission tomography/computerized tomography imaging ,3- Right after scanning and 4-Right before the patient is discharged. To determine the differences between the measurements, a statistical analysis was done. Results presented that the patients were injected 335.21±21 megabecquerel (MBq) (range: 199.8 - 525.4 MBq) of fluorine-18 deoxyglucose intravenously. The subjects remained for 120.9±15.77 min (range: 95 min-165 min) in the nuclear medicine department following IV fluorine-18 deoxyglucose injection. When measured from one meter, the radiation dose rates were 111.48 ±19.26 μSv/h following the injection, 39.58 ±10.05 μSv/h prior to the positron emission tomography/computerized tomography imaging, and 26.62±5.02 μSv/h right before the patients were discharged.It was determined that once the positron emission tomography/computerized tomography test was finished, measurements at a distance of one meter were suitable for discharge based on the Turkish Atomic Energy Authority regulation. Hence, after performing the fluorine-18 deoxyglucose positron emission tomography/computerized tomography and explaining the required safety measurements for radiation, patients can be discharged safe and sound.